Arithmetic-geometrical progression (AGP). Onyn kosyndysynyn formulas - Nurlybayev, Аманжол; Bekzhigitova, Ләззат (Рroblems of engineering and professional education, 2022)
In this article is considered guestions of receiving forms for first N-members amount of arithmetical-geometric progression